2016
DOI: 10.1002/eat.22573
|View full text |Cite
|
Sign up to set email alerts
|

Mammillary body volume abnormalities in anorexia nervosa

Abstract: Objective Several case reports of Wernicke’s Encephalopathy in AN due to thiamine deficiency have described mammillary body (MB) injury, but systematic studies are lacking. Here we evaluated whether underweight and weight-restored individuals with AN demonstrate evidence of abnormal MB morphology, via retrospective examination of a previously collected data set. Method Using standard-resolution T1-weighted magnetic resonance imaging at 3 Tesla, we measured MB volume and fornix area in a cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Thiamine deficiency occurs in 38% of individuals with AN, and is often unrecognized . Recently, selective brain volume alterations of the mammillary bodies have been linked to acute weight changes, reflecting a specific sensitivity to vitamin B1 deficiency of this brain area. Because of the high oxidative metabolism, it has earlier been suggested that the thalamic region, including the mammillary bodies, is particularly sensitive to thiamine deficiency A possible side‐effect of prolonged vitamin B1 deficiency is Wernicke's encephalopathy (WE).…”
mentioning
confidence: 99%
“…Thiamine deficiency occurs in 38% of individuals with AN, and is often unrecognized . Recently, selective brain volume alterations of the mammillary bodies have been linked to acute weight changes, reflecting a specific sensitivity to vitamin B1 deficiency of this brain area. Because of the high oxidative metabolism, it has earlier been suggested that the thalamic region, including the mammillary bodies, is particularly sensitive to thiamine deficiency A possible side‐effect of prolonged vitamin B1 deficiency is Wernicke's encephalopathy (WE).…”
mentioning
confidence: 99%
“…This tract is central for body distortion, a key feature in this disorder. There were no differences in the fornix in AN acute phase, but restored patients showed a significant difference only for the right fornix in the study by KhalsaKumar, Patel, Strober, and Feusner (2016) which, instead, found disparities in mammillary body volume of underweight AN patients, whereas it was increased in weight‐restored AN. Microstructural changes in the fornix of AN patients might have been biased by partial volume effects, as demonstrated by Kaufmann et al.…”
Section: White Matter Alterationsmentioning
confidence: 85%
“…31,33 In addition to signal changes, MB volume loss has also been reported in patients with anorexia nervosa as well as recovery of MB volume in individuals who regained weight. 30 Recovery of MB volume has also been reported in patients with acute liver failure following treatment with thiamine. 35 Furthermore, MB volume was found to correlate with blood thiamine levels.…”
Section: Mb Pathologymentioning
confidence: 92%
“…Wernicke encephalopathy in children typically arises from nutritional deficiency, which can occur due to vomiting (eg, due to anorexia nervosa, hyperemesis, gastrointestinal obstruction), [30][31][32] chronic gastrointestinal disease, 33 and following bariatric surgery. 34 Wernicke encephalopathy has also been reported following acute liver failure 35 and pancreatitis.…”
Section: Mb Pathologymentioning
confidence: 99%